2013
DOI: 10.1093/schbul/sbt120
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Associated With Late- and Very-Late-Onset Schizophrenia in the General Population: A Prospective Study

Abstract: Background: Individuals with autoimmune diseases and severe infections have persistent or acutely elevated inflammatory biomarkers and increased risk of schizophrenia. We tested the hypothesis that baseline elevated plasma levels of the inflammatory biomarker, C-reactive protein (CRP), associate with increased risk of late-and very-lateonset schizophrenia in the general population, and if such an association possibly is causal. Method: We analyzed data from 78 810 men and women, aged 20-100 years, from 2 large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 45 publications
6
59
4
1
Order By: Relevance
“…Of those, 76 were excluded on the basis of the title and the abstract, leaving 48 studies for further evaluation. Twenty-six studies fulfiled our inclusion criteria, 19 for the between-group meta-analysis of SZ versus control, 14,[17][18][19]21,24,25,[27][28][29][30][31][33][34][35][36]38,39,41 6 for the withingroup meta-analysis of CRP changes after initiation of antipsychotics 20,21,23,27,32,37 and 3 for the within-group metaanalysis of CRP changes with substitution of the type of the antipsychotic. 22,26,40 Some studies provided more than one pairwise comparison, as whenever possible we extracted data according to medication status.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of those, 76 were excluded on the basis of the title and the abstract, leaving 48 studies for further evaluation. Twenty-six studies fulfiled our inclusion criteria, 19 for the between-group meta-analysis of SZ versus control, 14,[17][18][19]21,24,25,[27][28][29][30][31][33][34][35][36]38,39,41 6 for the withingroup meta-analysis of CRP changes after initiation of antipsychotics 20,21,23,27,32,37 and 3 for the within-group metaanalysis of CRP changes with substitution of the type of the antipsychotic. 22,26,40 Some studies provided more than one pairwise comparison, as whenever possible we extracted data according to medication status.…”
Section: Resultsmentioning
confidence: 99%
“…3 Moreover, several cross-sectional studies and an early meta-analysis found increased inflammatory biomarkers, mostly cytokines, in the plasma and the serum of subjects with SZ. 11 Some inflammatory cytokines, 14 in particular interleukin 6 (IL-6) and interleukin 1β (IL-1β), have also been suggested to represent state markers for acute exacerbations of psychosis. 11 Taken together, these findings suggest that immune dysregulation may indeed be involved in the pathogenesis of SZ, and that SZ is a systemic disease with an inflammatory component (at least in patient subgroups) that could at least in part be responsible for common risk pathways in SZ and obesity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent prospective study demonstrated the association of C-reactive protein (CRP) measured on average of 7-8 years before hospitalization with schizophrenia or schizophrenia-like psychosis, with a 6-11-fold increased risk of late-and very-lateonset schizophrenia in the general population. 75 CRP is one of the most commonly used inflammation markers. The biological mechanism linking CRP and schizophrenia is not fully understood.…”
Section: Biochemical Findingsmentioning
confidence: 99%